2019
DOI: 10.1093/cid/ciz408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Anal High-grade Squamous Intraepithelial Lesions in Women Living with Human Immunodeficiency Virus

Abstract: Background Women living with human immunodeficiency virus (WLHIV) have disproportionately high rates of squamous cell carcinoma of the anus compared with the general population of women. Anal high-grade squamous intraepithelial lesions (HSILs) precede anal cancer, and accurate studies of HSIL prevalence among WLHIV in the United States are lacking. Methods The AIDS Malignancy Consortium 084 study was a multicenter national tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
3
25
4
2
Order By: Relevance
“…Among studies evaluating HSIL-AIN2+, one (4%) used cytology alone to diagnose HSIL+; 11 (48%) conducted HRA-directed biopsy on visible lesions, 8 (35%) conducted HRA among individuals with abnormal cytology with biopsies taken from visible lesions, and three (13%) studies took biopsies from individuals with both HRA-abnormal and normal findings. The highest scoring studies (≥5 on Newcastle-Ottawa scale, n=11) (30,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) included random biopsy of normal quadrants and/or an independent verification of histology (Appendix, page 32-33). Restricting analyses to these studies did not change the estimates, although there was weak evidence that ART was associated with lower risk of HSIL-AIN2+.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies evaluating HSIL-AIN2+, one (4%) used cytology alone to diagnose HSIL+; 11 (48%) conducted HRA-directed biopsy on visible lesions, 8 (35%) conducted HRA among individuals with abnormal cytology with biopsies taken from visible lesions, and three (13%) studies took biopsies from individuals with both HRA-abnormal and normal findings. The highest scoring studies (≥5 on Newcastle-Ottawa scale, n=11) (30,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) included random biopsy of normal quadrants and/or an independent verification of histology (Appendix, page 32-33). Restricting analyses to these studies did not change the estimates, although there was weak evidence that ART was associated with lower risk of HSIL-AIN2+.…”
Section: Resultsmentioning
confidence: 99%
“…All other authors declare no competing interests. (22, 23, 30-32, 34-36, 38, 41-43, 85-101) N populations 29 18 17 6 8 4 N PLHIV 7750 5311 4487 1107 2505 1745 ASCUS-AIN1+ prevalence (26-28, 32-35, 102-126) N populations 37 28 20 10 11 2 N PLHIV 8790 6782 5342 1720 2198 351 HSIL-AIN2+ prevalence (30,31,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137) N populations 23 15 16 6 5 7…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…HIV-infected men accounted for 96.0% of HSIL and 100% of AC cases in this study, while the study cohort consisted of 23% women. Recent studies among women living with HIV in US have reported the prevalence of anal HSIL to be 27% [ 19 ]. Our previous findings indicated that HIV-infected men had 7.9 times higher risk of incident anal HSIL (432 per 100,000 person-years), compared with HIV-infected women (55 per 100,000 person-years) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 23.3% of AC patients had median CD4 counts ≥500 (cells/μL) (Table 1 ) suggesting that a large proportion did not have optimal immune status prior to cancer diagnosis. Lower CD4 count (≤200 cells/μL) is known to be a key factor in anal HSIL and cancer development [ 19 , 25 ]. While CD4+ could be a proxy for HIV status or treatment effect, there are no standard guidelines for anal HSIL treatment so that could not be assessed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent national AIDS Malignancy Consortium (AMC084) trial study revealed that 28% of WLHIV have HSIL. 3 HSIL treatment using ablative therapies (i.e., infrared coagulation [IRC], electrocautery), topical treatments (i.e., 5% imiquimod or 5% fluorouracil cream) and continued surveillance, where HSIL recurrence may prompt further treatment, could prevent progression to SCCA. 4 Yet, to the best of our knowledge, recurrence rates (treatment effectiveness measure) among WLHIV remain unknown.…”
Section: Introductionmentioning
confidence: 99%